Preparation method of drag reducer for fracturing fluid
By using fluorinated acrylate-styrene-sulfonated polystyrene block copolymer with modified nano-silver particles as a drag reducer, the problem of high friction of carbon dioxide fracturing fluid during fracturing operations was solved, achieving both efficient proppant delivery and drag reduction, thereby improving the production and extraction efficiency of oil and gas wells.
Patent Information
- Application Number
- CN202411439250.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-07
AI Technical Summary
Existing carbon dioxide fracturing fluids have high friction during fracturing operations, making it impossible to balance drag reduction performance with proppant delivery capacity, resulting in reservoir damage and unsatisfactory development outcomes.
Fluorinated acrylate-styrene-sulfonated polystyrene block copolymer containing modified silver nanoparticles was used as a drag reducer. By adjusting the particle size and proportion of the silver nanoparticles, the molecular conformation and hydrodynamic properties of the copolymer were optimized, thereby improving the sand-carrying capacity and drag reduction effect of the fracturing fluid.
It improves the sand-carrying capacity of fracturing fluid, enhances drag reduction, reduces flow resistance, increases oil and gas well production and extraction efficiency, reduces proppant loss and waste, and lowers operating costs.
Abstract
Description
Technical Field
[0001] The invention relates to a carbon dioxide oil recovery technology, and in particular to a method for preparing a drag reducer for fracturing fluid. Background Art
[0002] Carbon dioxide flooding technology is a technology that injects carbon dioxide into oil layers to increase oil recovery. When carbon dioxide and formation crude oil first come into contact, they cannot form a miscible phase, but under the conditions of appropriate pressure, temperature and crude oil composition, carbon dioxide can form a miscible front. Supercritical fluid will extract heavier hydrocarbons from crude oil and continuously concentrate the gas at the front of the drive body. As a result, carbon dioxide and crude oil become miscible liquids, forming a single liquid phase, which can effectively displace formation crude oil to the production well.
[0003] However, carbon dioxide fracturing fluid also faces the problem of high friction during fracturing construction, which limits the scope of application of carbon dioxide fracturing fluid. As a result, some deeply buried low-permeability and highly water-sensitive reservoirs have to use conventional water-based fracturing fluid, causing permanent damage to the reservoir and unsatisfactory development results.
[0004] For example, the Chinese patent, application number, CN201810743824.6, a drag reducer for carbon dioxide dry fracturing and its application. The drag reducer mainly includes: a fluorinated acrylate polymer, a sulfonated polystyrene and a styrene block copolymer prepared by polymerization, wherein the mass ratio of the three is (55-65): (20-30): (10-20). The drag reducer has good compatibility with carbon dioxide. When dissolved in carbon dioxide fracturing fluid, it can reduce the friction resistance during fracturing, thereby reducing the surface pump pressure and the pressure of the pipeline, making the carbon dioxide dry fracturing project safer and the pipeline more able to meet the work requirements, increasing the speed of injecting liquid carbon dioxide, and enabling carbon dioxide dry fracturing to be used in deeper and more extreme reservoirs, and still maintaining a good drag reduction effect under more extreme conditions. The drag reduction effect can reach 30%-40% in fracturing operations.
[0005] However, it only reduces the friction resistance during fracturing and increases the transport capacity of carbon dioxide, but does not take into account the transport capacity of the proppant. Generally, the prior art often increases the viscosity of the drag reducer to increase the transport of the proppant, but this will result in poor performance of the drag reducer. Summary of the invention
[0006] The embodiment of the present application provides a method for preparing a drag reducer for fracturing fluid, thereby solving the problem in the prior art that both drag reduction performance and proppant transport performance cannot be taken into account, thereby achieving a balance between proppant transport and drag reduction capabilities.
[0007] The present application provides a method for preparing a drag reducer for fracturing fluid, the steps comprising: S1, preparing a silver-containing fluorinated acrylate polymer; S2, preparing silver-containing sulfonated polystyrene; S3, preparing a fluorinated acrylate-styrene-sulfonated polystyrene block copolymer; The silver-containing material specifically contains modified nano-silver particles.
[0008] Further, step S1 specifically comprises: mixing butyl methacrylate, isobornyl methacrylate and methyl methacrylate in a mass ratio of 1:1:1, and adding the mixture into a reaction kettle; Add hydrophobic modified nano silver particles so that the modified nano silver particles account for 1-3% of the total mass of the mixed monomers; add initiator azobisisobutyronitrile in an amount of 0.05% of the total mass of the mixed monomers to carry out the reaction; Dodecafluoroheptyl methacrylate accounting for 20% of the total mass of the mixed monomers is added, and the reaction is continued; a fluorinated acrylate polymer containing modified nanosilver particles is obtained.
[0009] Further, step S2 is specifically as follows: dissolving polystyrene in dichloroethane to form an organic solution; adding hydrophobic modified nanosilver particles so that the modified nanosilver particles account for 2-4% of the mass of the polystyrene; Slowly add concentrated sulfuric acid, the mass ratio of polystyrene to concentrated sulfuric acid is 90:10; react until sulfonated polystyrene containing modified nano-silver particles is obtained.
[0010] Further, step S3 specifically comprises: mixing water, fluorinated acrylate polymer containing modified nanosilver particles and styrene in a mass ratio of 20:50:30, and stirring evenly to obtain a mixed solution; adjusting the pH value of the mixed solution to 7-10; Sulfonated polystyrene containing modified nano-silver particles, as well as Na2S2O8 and Na2S2O3 as initiators, with the initiator addition amount being 0.06% of the total mass, is added to carry out a polymerization reaction; a fluorinated acrylate-styrene-sulfonated polystyrene block copolymer containing modified nano-silver particles is obtained.
[0011] Furthermore, the preparation method of the modified nano silver particles is: Silver nitrate solution is used as a silver precursor, and sodium citrate solution is slowly added as a reducing agent under stirring conditions. After the reaction, sodium dodecyl sulfate solution is added to the reaction system to enhance the hydrophobicity of the nanoparticles. After the reaction is completed, nanosilver particles are obtained by centrifugation, washing and drying. The nanosilver particles are dispersed in an ethanol solution containing 0.5% by mass fraction of trimethylchlorosilane, and the reaction is stirred at room temperature for 4 hours to obtain modified nanosilver particles. The particle size of the modified nanosilver particles is 10-50nm.
[0012] Further, the reaction conditions are 75-80°C for 1-3 hours, specifically including step S1 after adding the initiator, step S2 after adding dodecafluoroheptyl methacrylate, and step S3 after adding the initiator; in step S2, the reaction temperature is 40°C after adding concentrated sulfuric acid.
[0013] Furthermore, the reaction conditions are 60-70°C, and the reaction time is extended to 4-6h, specifically including step S1 after adding the initiator, step S2 after adding dodecafluoroheptyl methacrylate, and step S3 after adding the initiator; in step S2, the reaction temperature is 30°C after adding concentrated sulfuric acid.
[0014] Furthermore, the modified nano-silver particles added during the polymerization of the fluorinated acrylate polymer and the sulfonated polystyrene also include large-particle modified nano-silver particles and small-particle modified nano-silver particles; the particle size of the large-particle modified nano-silver particles is 100nm-300nm; the particle size of the small-particle modified nano-silver particles is 10nm-30nm; the mass ratio of the large-particle modified nano-silver particles to the small-particle modified nano-silver particles is 1:(3-7).
[0015] Furthermore, the modified nano-silver particles added during the preparation of the fluorinated acrylate polymer and the sulfonated polystyrene are one of large-diameter modified nano-silver particles and small-diameter modified nano-silver particles.
[0016] Furthermore, when the fluorinated acrylate polymer is used to modify the nanosilver particles with large particle size, the sulfonated polystyrene is used to modify the nanosilver particles with small particle size; when the fluorinated acrylate polymer is used to modify the nanosilver particles with small particle size, the sulfonated polystyrene is used to modify the nanosilver particles with large particle size.
[0017] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, the sand-carrying capacity of the fracturing fluid mainly depends on its viscosity, density and flow properties; nanosilver particles improve the sand-carrying capacity of the fracturing fluid, enabling it to more effectively transport proppants (such as sand particles) into the cracks, thereby improving the conductivity of the cracks and the production of oil and gas wells; reducing the loss and waste of proppants, reducing operating costs, and improving the production efficiency of oil and gas wells; the addition of nanosilver particles changes the molecular conformation and fluid mechanics of the copolymer, thereby affecting the flow resistance of the fracturing fluid in the pipeline. At the same time, the surface effect of the nanosilver particles also contributes to the drag-reducing effect of the fracturing fluid, reducing the flow resistance of the fracturing fluid in the pipeline, improving its transportation efficiency, and reducing energy consumption and equipment wear during the pumping process.
[0018] Secondly, due to the close encapsulation of the polymer and the nano-silver particles, the drag reducer is more evenly dispersed in the fracturing fluid, which can more effectively reduce the frictional resistance of the fluid in the pipeline; the close encapsulation of the nano-silver particles also reduces their shedding and agglomeration during the fracturing process, thereby maintaining the stability of the drag reduction effect; lowering the polymerization temperature and extending the polymerization time help to reduce the breakage and recombination of the polymer chain, thereby improving the stability of the drag reducer; the tight encapsulation structure also makes the drag reducer more resistant to the influence of harsh environments such as high temperature and high pressure on the polymer chain; although the changes in polymerization temperature and time have limited direct effects on the sand carrying capacity, the enhanced drag reduction effect and improved stability indirectly help to improve the sand carrying capacity, and the more even dispersion and stable drag reduction effect enable the fracturing fluid to more effectively transport the proppant into the cracks.
[0019] Third, when both fluorinated acrylate polymer and sulfonated polystyrene use a combination of large and small particles, a synergistic effect may occur between particles of different sizes. The combination of large and small particles can produce a synergistic drag reduction effect. Large particles form a stable vortex structure in the fluid to reduce turbulent resistance; while small particles can fill the gaps between large particles, further smoothing the fluid flow path, thereby reducing overall resistance. Small particles significantly increase the total surface area of the particles, increase the interaction area between the particles and the fluid, and further enhance the drag reduction effect.
[0020] Fourth, by precisely controlling the size of polymer-encapsulated silver particles and adjusting the proportions of fluorinated acrylate polymer (FAP) and sulfonated polystyrene (SPS) in the block copolymer, the function of the copolymer can be significantly affected, thereby optimizing the oil recovery effect of the carbon dioxide fracturing fluid. DETAILED DESCRIPTION
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items. Embodiment 1
[0022] The present application discloses a method for preparing a drag reducer for fracturing fluid, comprising: S1, preparing a silver-containing fluorinated acrylate polymer; Specifically, butyl methacrylate, isobornyl methacrylate and methyl methacrylate are mixed in a mass ratio of 1:1:1 and added into a reaction kettle; Add hydrophobic modified nanosilver particles so that the modified nanosilver particles account for 1-3% of the total mass of the mixed monomers; add initiator azobisisobutyronitrile in an amount of 0.05% of the total mass of the mixed monomers; react at 75-80° C. for 1-3 hours; Add dodecafluoroheptyl methacrylate (accounting for 20% of the total mass of the mixed monomers), and continue to react at 75-80° C. for 1-3 hours to obtain a fluorinated acrylate polymer containing modified nanosilver particles; S2, preparing silver-containing sulfonated polystyrene; Specifically, polystyrene is dissolved in ethylene dichloride to form an organic solution; hydrophobic modified nanosilver particles are added so that the modified nanosilver particles account for 2-4% of the mass of the polystyrene; Slowly adding concentrated sulfuric acid, the mass ratio of polystyrene to concentrated sulfuric acid being 90:10; reacting at 40° C. until sulfonated polystyrene containing modified nanosilver particles is obtained; S3, preparing a fluorinated acrylate-styrene-sulfonated polystyrene block copolymer; Specifically, an appropriate amount of water, a fluorinated acrylate polymer containing modified nanosilver particles, and styrene are mixed in a mass ratio of 20:50:30, and stirred evenly to obtain a mixed solution; and the pH value of the mixed solution is adjusted to 7-10; Adding sulfonated polystyrene containing modified nano-silver particles, and Na2S2O8 and Na2S2O3 as initiators, the amount of initiator added being 0.06% of the total mass; performing polymerization reaction at 75-80° C. for 1-3 hours; obtaining a fluorinated acrylate-styrene-sulfonated polystyrene block copolymer containing modified nano-silver particles; Wherein, the preparation method of modified nano silver particles is: Silver nitrate solution is used as a silver precursor, and sodium citrate solution is slowly added as a reducing agent under stirring conditions. After the reaction, sodium dodecyl sulfate solution is added to the reaction system to enhance the hydrophobicity of the nanoparticles. After the reaction is completed, nanosilver particles are obtained by centrifugation, washing and drying. The nanosilver particles are dispersed in an ethanol solution containing 0.5% by mass fraction of trimethylchlorosilane, and the reaction is stirred at room temperature for 4 hours to obtain modified nanosilver particles. The particle size of the modified nanosilver particles is 10-50nm.
[0023] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The sand-carrying capacity of fracturing fluid mainly depends on its viscosity, density and flow properties; nanosilver particles improve the sand-carrying capacity of fracturing fluid, enabling it to more effectively transport proppants (such as sand particles) into fractures, improve fracture conductivity and oil and gas well production; reduce proppant loss and waste, reduce operating costs, and improve oil and gas well production efficiency; The addition of nanosilver particles changes the molecular conformation and fluid mechanics of the copolymer, thus affecting the flow resistance of the fracturing fluid in the pipeline. At the same time, the surface effect of the nanosilver particles also contributes to the drag reduction effect of the fracturing fluid, reducing the flow resistance of the fracturing fluid in the pipeline, improving its delivery efficiency, and reducing energy consumption and equipment wear during pumping. During the preparation process, the nanosilver particles are encapsulated in the fluorinated acrylate-styrene-sulfonated polystyrene block copolymer. This structure allows the nanosilver particles to be stably present in the copolymer and is not easy to fall off or agglomerate, thereby maintaining its good performance; and the fluorinated acrylate-styrene-sulfonated polystyrene block copolymer can better combine with the carbon dioxide fracturing fluid and produce a drag reduction effect. The combination of the two can not only improve the drag reduction effect but also improve the transport of the proppant; Nanosilver particles themselves have a certain lubricity, which can reduce the frictional resistance of the fluid in the pipeline; when the nanosilver particles are encapsulated in the fluorinated acrylate-styrene-sulfonated polystyrene block copolymer, a more uniform dispersion system can be formed, further enhancing the lubricity of the fluid, thereby reducing the energy loss during the fracturing process; Fluorinated acrylate-styrene-sulfonated polystyrene block copolymer itself has the ability to change the wettability of rock surfaces, and the nano-silver particles further enhance this effect, making it easier for fracturing fluid to penetrate into the reservoir and improve oil recovery efficiency; the nano-silver particles also have a certain catalytic effect, accelerating the oil-water separation process and further improving oil recovery efficiency; Nanosilver particles have good antioxidant properties and can protect polymers from oxidative degradation, thereby improving the stability of fracturing fluids. Nanosilver particles improve the temperature resistance of polymers, allowing them to maintain stable performance in high-temperature and high-pressure fracturing environments, and maintain high efficiency after long periods of high temperature. Due to the enhanced drag reduction effect, the energy loss required in the fracturing process is reduced, thereby improving the fracturing efficiency; the improvement in oil recovery efficiency directly increases crude oil production; the enhanced stability enables the fracturing fluid to maintain excellent performance for a longer period of time, reducing the frequency and cost of replacing the fracturing fluid. Embodiment 2
[0024] The above embodiment adds modified nanosilver particles during the polymerization process of fluorinated acrylate polymer and sulfonated polystyrene to obtain a fluorinated acrylate-styrene-sulfonated polystyrene block copolymer containing nanosilver particles, so that when used as a drag reducer, it not only improves the drag reduction effect and increases the viscosity, but also reduces the friction with the pipe wall and improves the transport capacity of the proppant. In order to improve the degree of bonding between the polymer and the nanosilver particles, further improvements are made on the basis of Example 1.
[0025] By lowering the polymerization temperature and prolonging the polymerization time, the tightness of the polymer wrapping silver can be increased; Specifically: lower the polymerization reaction temperature to 60-70°C, extend the reaction time to 4-6h, wherein the reaction temperature of step S2 is lowered to 30°C.
[0026] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Due to the close encapsulation of polymer and nano-silver particles, the drag reducer is more evenly dispersed in the fracturing fluid, which can more effectively reduce the friction resistance of the fluid in the pipeline; the close encapsulation of nano-silver particles also reduces their shedding and agglomeration during the fracturing process, thereby maintaining the stability of the drag reduction effect; lowering the polymerization temperature and extending the polymerization time help reduce the breakage and recombination of polymer chains, thereby improving the stability of the drag reducer; the tight encapsulation structure also makes the drag reducer more resistant to the influence of harsh environments such as high temperature and high pressure on the polymer chain; although the changes in polymerization temperature and time have limited direct effects on the sand carrying capacity, the enhancement of the drag reduction effect and the improvement of stability indirectly help to improve the sand carrying capacity, and the more even dispersion and stable drag reduction effect enable the fracturing fluid to more effectively transport the proppant into the cracks; The enhanced drag reduction effect and improved sand carrying capacity have jointly improved fracturing efficiency, thereby increasing the production of oil and gas wells. The stable drag reduction effect reduces energy loss and equipment wear caused by increased resistance during fracturing, thereby reducing operating costs. The efficient sand carrying capacity reduces the loss and waste of proppants, further reducing costs. Reducing energy loss and equipment wear also means less carbon emissions and environmental pollution, which is in line with the current trend of environmental protection and energy conservation. Embodiment 3
[0027] Example 2 reduces the polymerization temperature, prolongs the polymerization time, and increases the tightness of the polymer wrapping silver, thereby more effectively reducing the friction resistance of the fluid in the pipeline; in order to improve the stability of the drag reducer, modified nano-silver particles of different particle sizes are used in combination, which is further improved on the basis of Example 2.
[0028] Modified nano silver particles added during the polymerization of fluorinated acrylate polymer and sulfonated polystyrene, including large modified nano silver particles and small modified nano silver particles; The particle size of large particle modified nano silver particles is 100nm-300nm; The particle size of small modified nanosilver particles is 10nm-30nm; The mass ratio of the large-particle modified nanosilver particles to the small-particle modified nanosilver particles is 1:(3-7).
[0029] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Large particles provide stronger mechanical strength and better wear resistance, reducing the degradation of drag reducers under high pressure environments; small particles have a higher specific surface area, increasing the contact area with the fluid, thereby improving the drag reduction effect; When both fluorinated acrylate polymer and sulfonated polystyrene use a combination of large and small particles, there may be a synergistic effect between particles of different sizes. The combination of large and small particles can produce a synergistic drag reduction effect. Large particles form a stable vortex structure in the fluid to reduce turbulent resistance; while small particles can fill the gaps between large particles, further smoothing the fluid flow path, thereby reducing overall resistance. Small particles significantly increase the total surface area of the particles, increase the interaction area between the particles and the fluid, and further enhance the drag reduction effect. Small particles can more effectively fill the gaps between large particles, reduce particle agglomeration, improve the dispersion of particles in fracturing fluid, maintain the long-term stability of the drag reducer, and reduce the change of performance over time; the combination of large and small particles can improve the anti-sedimentation performance of particles. Large particles provide structural support, while small particles increase the interaction between particles to jointly resist sedimentation and stratification. The interaction between large and small particles forms a more stable particle network structure, which can better carry and disperse the distribution of proppants (such as sand particles) in the fracturing fluid; by optimizing the particle size distribution, the flow characteristics of the fracturing fluid are improved, so that the proppants can be more evenly distributed in the cracks and the sand carrying capacity is improved; Since the combined use of large and small particles can produce a stronger drag reduction effect, the amount of drag reducer used can be reduced, thereby reducing costs. The enhanced drag reduction effect and optimized sand carrying capacity together improve the fracturing efficiency, thereby increasing the production of oil and gas wells. The combined use of large and small particles may be easier to recycle and reuse, thereby improving the sustainability of the material. Embodiment 4
[0030] Embodiment 3 further improves its drag reduction capability and stability through the combination of large and small particles. In order to improve environmental adaptability, further improvements are made on the basis of Embodiment 3.
[0031] The function of the block copolymer can be affected by controlling the proportion of fluorinated acrylate polymer and sulfonated polystyrene in the block copolymer through the particle size of polymer-wrapped silver, and different block copolymers can be designed according to the environment.
[0032] Specifically, the modified nano-silver particles added during the preparation of the fluorinated acrylate polymer and the sulfonated polystyrene are either large-diameter modified nano-silver particles or small-diameter modified nano-silver particles; Wherein, when the fluorinated acrylate polymer uses large-size modified nano-silver particles, the sulfonated polystyrene uses small-size modified nano-silver particles; when the fluorinated acrylate polymer uses small-size modified nano-silver particles, the sulfonated polystyrene uses large-size modified nano-silver particles; The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: By precisely controlling the size of polymer-encapsulated silver particles and adjusting the ratio of fluorinated acrylate polymer (FAP) and sulfonated polystyrene (SPS) in the block copolymer, the function of the copolymer can be significantly affected, thereby optimizing the oil recovery effect of CO2 fracturing fluid, such as: Large-particle FAP + small-particle SPS: Large-particle FAP provides excellent weather resistance and mechanical strength, which helps the fracturing fluid remain stable under high pressure, while small-particle SPS, due to its high specific surface area and reactivity, can more effectively reduce the oil-water interfacial tension, promote the stripping and flow of crude oil, and significantly improve the oil recovery efficiency; The modified nanosilver particles with large particle size play the role of strengthening the skeleton in FAP, improving the mechanical strength and shear resistance of the copolymer, making the fracturing fluid less likely to break during high-pressure injection and maintaining stable flow properties; the SPS with small particle size is more evenly dispersed in the fracturing fluid, which can effectively improve the fluidity and permeability of the fracturing fluid, making it easier for it to enter tiny rock pores and improve the recovery rate of crude oil; Small-size FAP+large-size SPS: Due to its smaller particle size and higher specific surface area, small-size FAP can be more effectively adsorbed on the oil-water interface, significantly reducing interfacial tension, improving the wettability of the rock surface, and making it easier for the water phase to penetrate into the rock pores, thereby improving the oil recovery efficiency; the combination of small-size FAP and large-size SPS can form a multi-scale interfacial active system. Small-size FAP is responsible for reducing interfacial tension, while large-size SPS may change the oil-water distribution on a larger scale through its amphiphilic properties. The two work synergistically to further enhance the oil recovery effect.
[0033] Small-particle FAP is easier to disperse in the fracturing fluid and can form finer pore channels, which helps the fracturing fluid to better penetrate into the tiny pores of the rock. This is particularly important for low-permeability oil fields, because tiny pores are often the main storage space for residual oil. Although the SPS particle size is large, its unique amphiphilic properties enable it to form a good support structure in the rock pores, preventing the leakage and loss of the fracturing fluid during the flow process, thereby improving the utilization rate of the fracturing fluid and the oil recovery effect. Large-particle SPS usually has better mechanical strength and shear resistance due to its larger particle size and higher molecular weight. During the injection of fracturing fluid, large-particle SPS can resist the effect of high-pressure shear force, maintain the stability of the fracturing fluid, and prevent it from premature gel breakage or degradation; although small-particle FAP has low mechanical strength, its excellent surface activity and dispersion properties prevent the aggregation and sedimentation of solid particles in the fracturing fluid, thereby maintaining the stability of the fracturing fluid together with large-particle SPS.
[0034] Drag reduction rate test: Towards 10 4 The fracturing fluid drag reducer was added to the high-mineralization brine with a drag reducer concentration of 0.8 g / L, and the drag reduction rate test was carried out. The calcium ion concentration in the high-mineralization brine was 1000 mg / L, the magnesium ion solubility was 200 mg / L, the sodium ion solubility was 3200 mg / L, and the chloride ion concentration was 5600 mg / L; the shear rate was 170 s -1 , shear time is 30min, temperature is 25℃; drag reduction rate η=1-△P / P0, P0 is the water pressure drop before adding fracturing fluid drag reducer, unit is Pa; △P is the water pressure drop after adding fracturing fluid drag reducer, unit is Pa.
[0035] Thermal stability: The fracturing fluid drag reducer was added to test the viscosity at 25°C, recorded as A0. The fracturing fluid drag reducer was stored at 90°C for 30 days and the viscosity was tested again, recorded as A1. The viscosity retention rate = A1 / A0×100%. The results are shown in Table 1.
[0036] SPS silver content (%) FAP silver content (%) High mineralization brine drag reduction rate η (%) Viscosity retention rate (%) Embodiment 1 1 2 72.5 83.2 2 3 73.5 85.2 3 4 75.1 86.2 Embodiment 2 2 3 78.3 88.1 Embodiment 3 2 3 84.2 92.3 Embodiment 4 2 (large particles) 3 (small particles) 86.2 93.1 Table 1 The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a drag reducer for fracturing fluid, characterized in that the steps include: S1, preparing a silver-containing fluorinated acrylate polymer; S2, preparing silver-containing sulfonated polystyrene; S3, preparing a fluorinated acrylate-styrene-sulfonated polystyrene block copolymer; The silver-containing material specifically contains modified nano-silver particles.
2. The method for preparing a drag reducer for fracturing fluid according to claim 1, characterized in that: Step S1 specifically comprises: mixing butyl methacrylate, isobornyl methacrylate and methyl methacrylate in a mass ratio of 1:1:1, and adding the mixture into a reaction kettle; Add hydrophobic modified nano silver particles so that the modified nano silver particles account for 1-3% of the total mass of the mixed monomers; add initiator azobisisobutyronitrile in an amount of 0.05% of the total mass of the mixed monomers to carry out the reaction; Dodecafluoroheptyl methacrylate accounting for 20% of the total mass of the mixed monomers is added, and the reaction is continued; a fluorinated acrylate polymer containing modified nanosilver particles is obtained.
3. The method for preparing a drag reducer for fracturing fluid according to claim 1, characterized in that: Step S2 specifically comprises: dissolving polystyrene in ethylene dichloride to form an organic solution; adding hydrophobic modified nano-silver particles so that the modified nano-silver particles account for 2-4% of the mass of the polystyrene; Slowly add concentrated sulfuric acid, the mass ratio of polystyrene to concentrated sulfuric acid is 90:10; react until sulfonated polystyrene containing modified nano-silver particles is obtained.
4. The method for preparing a drag reducer for fracturing fluid according to claim 1, characterized in that: Step S3 specifically comprises: mixing water, fluorinated acrylate polymer containing modified nanosilver particles and styrene in a mass ratio of 20:50:30, and stirring evenly to obtain a mixed solution; adjusting the pH value of the mixed solution to 7-10; Sulfonated polystyrene containing modified nano-silver particles, as well as Na2S2O8 and Na2S2O3 as initiators, with the initiator addition amount being 0.06% of the total mass, is added to carry out a polymerization reaction; a fluorinated acrylate-styrene-sulfonated polystyrene block copolymer containing modified nano-silver particles is obtained.
5. The method for preparing a drag reducer for fracturing fluid according to claim 1, characterized in that: The preparation method of modified nano silver particles is: Silver nitrate solution is used as a silver precursor, and sodium citrate solution is slowly added as a reducing agent under stirring conditions. After the reaction, sodium dodecyl sulfate solution is added to the reaction system to enhance the hydrophobicity of the nanoparticles. After the reaction is completed, nanosilver particles are obtained by centrifugation, washing and drying; the nanosilver particles are dispersed in an ethanol solution containing 0.5% by mass of trimethylchlorosilane, and stirred for reaction at room temperature for 4 hours to obtain modified nanosilver particles; the particle size of the modified nanosilver particles is 10-50nm.
6. The method for preparing a drag reducer for fracturing fluid according to claim 1, characterized in that: The reaction conditions are 75-80° C. for 1-3 hours, specifically including step S1 after adding the initiator, step S2 after adding dodecafluoroheptyl methacrylate, and step S3 after adding the initiator; in step S2, the reaction temperature is 40° C. after adding concentrated sulfuric acid.
7. The method for preparing a drag reducer for fracturing fluid according to claim 1, characterized in that: The reaction conditions are 60-70°C, and the reaction time is extended to 4-6h, specifically including step S1 after adding the initiator, step S2 after adding dodecafluoroheptyl methacrylate, and step S3 after adding the initiator; in step S2, the reaction temperature is 30°C after adding concentrated sulfuric acid.
8. The method for preparing a drag reducer for fracturing fluid according to claim 7, characterized in that: The modified nano silver particles added during the polymerization of fluorinated acrylate polymer and sulfonated polystyrene also include large modified nano silver particles and small modified nano silver particles; the particle size of the large modified nano silver particles is 100nm-300nm; the particle size of the small modified nano silver particles is 10nm-30nm; the mass ratio of the large modified nano silver particles to the small modified nano silver particles is 1: (3-7).
9. The method for preparing a drag reducer for fracturing fluid according to claim 8, characterized in that: The modified nano silver particles added in the preparation process of the fluorinated acrylate polymer and the sulfonated polystyrene are one of large-diameter modified nano silver particles and small-diameter modified nano silver particles.
10. The method for preparing a drag reducer for fracturing fluid according to claim 9, characterized in that: When the fluorinated acrylate polymer is used to modify the nanosilver particles with large particle size, the sulfonated polystyrene is used to modify the nanosilver particles with small particle size. When the fluorinated acrylate polymer is used to modify the nanosilver particles with small particle size, the sulfonated polystyrene is used to modify the nanosilver particles with large particle size.
Citation Information
Patent Citations
A drag-reducing agent for dry carbon dioxide fracturing and its application
CN108864387B
High-molecular nanoparticle gas pipeline corrosion inhibition type drag reducer and its preparation method
CN102952287A
Low-friction drag composite nano-proppant and preparation method thereof
CN108517205A
Nanometer macromolecular drag reducer
CN113202998A